Factors that Determine the Performance of Carbon Fuels in the Direct Carbon Fuel Cell - Li, X.; Zhu, Z.; De Marco, Roland; Dicks, A.; Bradley, J.; Liu, S.; Lu, G. (American Chemical Society, 2008)
The direct carbon fuel cell (DCFC) is a promising power generation device, which has a much higher efficiency (80%) and a lower emission than conventional coal-fired power plants. In this study, different commercial carbon fuels including activated carbon (AC), carbon black (CB220 and CB660), and graphitic carbon (GC) were tested in DCFC at 600-800 C. The relationship between the intrinsic properties of carbon fuels and their electrochemical performance in the DCFC was analyzed. It is found that a desirable carbon fuel for DCFC should have high mesoporous surface area and rich oxygen-containing surface groups. The anodic performance of the DCFC may also be improved by small carbon particle size, fast stirring rates, and high cell temperatures.